Haj to Utopia : How the Ghadar Movement Charted Global Radicalism and Attempted to Overthrow the British Empire. - Ramnath, Maia, 1973- (California world history library, 2011)
In The Haj to Utopia, Maia Ramnath tells the dramatic story of Ghadar, the Indian anticolonial movement that attempted overthrow of the British Empire. Founded by South Asian immigrants in California, Ghadar--which is translated as "mutiny"--Quickly became a global presence in East Asia, Europe, the Middle East, and East Africa. Ramnath brings this epic struggle to life as she traces Ghadar's origins to the Swadeshi Movement in Bengal, its establishment of headquarters in Berkeley, California, and its fostering by anarchists in London, Paris, and Berlin. Linking Britain's declaration of war on G